William Whiston: No Longer an Arian. Issue 4 (2nd September 2015) - GILLIAM, PAUL R.
<x content-type="archive" xml:space="preserve">Abstract</x> This article contends that William Whiston (1667–1752) has been misidentified as an Arian for more than three hundred years. Though Whiston was labelled an Arian by his theological opponents, and early in his career naively accepted the Arian label for his own Christological beliefs, he consistently demarcated his own beliefs from those of Arius of Alexandria and Eusebius of Nicomedia. Furthermore, Whiston agreed with the Council of Nicaea's decision to rule Arius' understanding of the relationship of the Son to the Father out of bounds. Thus, William Whiston should no longer be called an Arian.